Behavioural intention of tourists towards volunteer tourism: A developing country perspective - Shahzar Ali Khan; Verda Khan; Mohd Asif Khan (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: Although volunteer tourism has been studied via several theoretical lenses, little is known about the behavioural intention of potential volunteer tourists from developing nations. This study aimed to identify the behavioural intention of potential volunteer tourists and the factors motivating them. This study extends the theory of planned behaviour (TPB) to identify the potential volunteer tourists' behavioural intentions by adding four motivations: altruism, personal development, escape, and travel. Methods: A total of 272 valid responses were collected through an online survey. SmartPLS 3.0 was used to test the hypotheses. Results: The findings indicate that attitude, perceived behavioural control, subjective norms, escape, and personal development positively influences potential volunteer tourists' intention to take part in volunteer tourism programs. However, altruism and travel do not influence the potential volunteer tourists' intention to take part in volunteer tourism programs. Implications: Volunteer tourism organisers will get help from the present study's findings to design or improve volunteer tourism programs and activities accordingly, resulting in improved volunteer tourism experiences and, ultimately, impacting the tourists' intention to take part in volunteer tourism programs.
Keywords: L83; L52; E7; 330; Volunteer tourism; Theory of planned behaviour; Behavioural intention